Lumbopelvic sagittal standing posture associations with anthropometry, physical activity levels and trunk muscle endurance in healthy adults - George A. Koumantakis; Antonios Malkotsis; Stefanos Pappas; Maria Manetta; Timotheos Anastopoulos; Apollon Kakouris; Eleutherios Kiourtsidakis (World Scientific Publishing, 2021)
Background: Various factors, inherited and acquired, are associated with habitual spinal postures. Objective: The purpose of this study was to identify the relationships between trunk muscle endurance, anthropometry and physical activity/inactivity and the sagittal standing lumbopelvic posture in pain-free young participants. Methods: In this study, 112 healthy young adults (66 females), with median (IQR) age of 20 years (18.2-22 years), without low back pain, injury or trauma were included. Lumbar curve (LC) and sacral slope (SS) angles were measured in standing with a mobile phone application (iHandy level). Anthropometric, physical activity/inactivity levels (leisure-time sport involvement and sitting hours/day) and abdominal (plank prone bridge test) and paraspinal (Sorensen test) isometric muscle endurance measures were collected. Results: LC and SS angles correlated significantly (r=0.80, p<0.001). Statistically significant differences for both LC (p=0.023) and SS (p=0.013) angles were identified between the male and female participants. A significant negative correlation was identified between the abdominal endurance time and LC (r=−0.27, p=0.004); however, the power of this result (56%) was not sufficiently high. The correlation between abdominal endurance and SS was non-significant (r=−0.17, p=0.08). In addition, no significant associations were identified between either of the sagittal lumbopelvic angles (LC-SS) in standing and the participants' body mass index (BMI), paraspinal endurance, leisure-time sport involvement or sitting hours/day. Conclusion: The potential role of preventive exercise in controlling lumbar lordosis via enhancement of the abdominal muscle endurance characteristics requires further confirmation. A subsequent study, performed in a larger population of more diverse occupational involvement and leisure-time physical activity levels, is proposed.